Analysis of Deformation Behavior of C15000 during Multi Profile Die Extrusion and Optimization of Process Parameters - Elias, Dessie (ASTU, 2022)
Copper Alloy Is One Of The Most Versatile Engineering Materials. Among Various Grades Of Copper,C15000 Is Getting Much More Attention In Various Electrical And Optical Applications. But As Far As The Formability And Strength Of These Particular Grades Are Concerned, There Is A Lack Of Necessary Data And Research. Much Research Has Been Carried Out On Aluminum Alloy Multi-Profile Die Extrusion While There Is A Shortage Of Research On Copper Alloy C15000 Extrusion. Therefore, The Present Thesis Aims To Enhance The Capability Of C15000 Through A Multi-Profile Extrusion Process And Further Evaluation Of Formability Process Parameters Optimization. Numerical Analysis Was Carried Out By Finite Element Analysis Tool (Deform- 3d). The Mathematical Modeling And Multi-Objective Optimization Of The Process Parameters For The Optimal Value Of Output Were Carried Out Through Multi Response Surface Methodology. The Fabrication Of The Extrusion Die And Container Was Carried Out As Per The Results Of The Numerical Simulation. At Optimized Process Parameters; Z-Load Of 31370n, 33860 N, And 34940 N. Whereas; The Effective Stresses Of 55.7 Mpa, 55.7mpa, And 55.2 Mpa While Damage Of The Billet Were 0.425 For Cosine, 0.4435 For Streamline And 0.498 Lc Die Profiles. The Experimental Investigation (Extrusion Of Billet Material Of C15000 Grade) Was Carried Out On A Hydraulic Press Machine. Testing And Characterization Of Both Commercial And Extruded Products Have Been Done Using Mechanical And Metallurgical Testing Machines. The Compression Strength Of The Linear Convergent Die Extruded Sample Is Slightly Lower Than That Of The Cosine Die Extruded Sample But Much Higher Than That Of The Commercially Available Sample. The Hardness Of The Commercially Available Specimen Is 133.9hv. The Hardness Increases To 161.6hv And 162.8hv, Respectively As The Specimen Is Extruded In Linear Convergent And Cosine Die Profiles, And Microstructural Analysis Shows The Microstructures Of The Extruded Products Are Obviously Refined And Evenly Distributed In The Deformed Products.
Keywords: ulti response surface Methodology, Finite element analysis, Extrusion, Die-profile, Optimization